Investigation of Entrepreneurial Values Through Business Program at Gudo Vocational School, Jombang District - Deni Alimaningtyas; Mohammad Syukri Ghozali (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to evaluate the instillation of entrepreneurial values through the Business Program at Gudo Vocational School, Jombang Regency. Through a qualitative approach, observations and in-depth interviews with 50 students, teachers and school management, this research highlights the impacts and challenges faced in implementing the program. The research results show that the Business Program has succeeded in increasing entrepreneurial awareness among students, with more than 80% of respondents indicating an increased understanding of the essence of entrepreneurship. However, challenges such as the lack of integration between theory and practice in the curriculum and the need for more mentor support and guidance in developing business ideas are highlighted. Recommendations for this research include expanding direct practice, increasing theory-practice integration, and strengthening the role of mentors to support the development of students' entrepreneurial ideas and skills at Gudo Vocational School, Jombang Regency.